Insecure Housing and the Ongoing Search for Ontological Security: How Low-Income Older Women Cope. Issue 2 (15th March 2023) - Power, Emma R.
ABSTRACT: The paper examines how people experiencing persistent housing insecurity hold on to or restore ontological security. Conceptually it recognises ontological security as an "ongoing accomplishment" that is "actively sought", and introduces four coping constructs theorised by Giddens as ways that individuals cope with persistent threats to security. The domestic practices of low-income, single older women living in various forms of insecure housing in Australia are the focus. The paper identifies "emotion-focused" and "action-focused" strategies through which women sought ontological security, including efforts to mentally accommodate insecurity, tenancy practices, through which they engaged with housing risk, and the use of storage facilities as holding sites of identity and routine. These strategies resonate with and extend Giddens' four coping constructs to the housing field, reflecting pragmatic acceptance of housing risk, sustained optimism in the face of housing risk, cynical pessimism, and engagement with housing risk. The paper reveals dynamic and fraught relations between home and ontological security that are frequently an exercise in cruel optimism.